2019
DOI: 10.3889/oamjms.2019.179
|View full text |Cite
|
Sign up to set email alerts
|

Safety Profile and Efficacy of Chemoembolization with Doxorubicin - Loaded Polyethylene Glycol Microspheres in Patients with Hepatocellular Carcinoma

Abstract: AIM: This study was designed as a preliminary investigation of safety and efficacy of LifePearl, polyethylene glycol microspheres loaded with doxorubicin for treatment of locally untreatable (i.e., unresectable and not suitable for local thermal ablation) hepatocellular carcinoma (HCC). MATERIAL AND METHODS: Patients with locally untreatable HCC (mono- or bilobar disease, ECOG performance status 0-1, Chilg-Pugh score < 11) were analysed for this single arm Unicenter retrospective study. All the inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…Treatment with LifePearl™ was well tolerated in the authors' study and agreed with the findings of several previous studies, which demonstrated good procedure safety and AEs of mild intensity (e.g., postembolic syndrome and fever) [6,[17][18][19][20][21][22][23][24][25]. Liver toxicity with TACE with doxorubicin-loaded microspheres was usually reflected by increases in AST, GGT, ALT and bilirubin levels [6,23,24]. The results of this study showed that AST, ALT and GGT levels did not change significantly after TACE compared with baseline, whereas ALK levels significantly increased versus baseline (though never exceeding normal values).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Treatment with LifePearl™ was well tolerated in the authors' study and agreed with the findings of several previous studies, which demonstrated good procedure safety and AEs of mild intensity (e.g., postembolic syndrome and fever) [6,[17][18][19][20][21][22][23][24][25]. Liver toxicity with TACE with doxorubicin-loaded microspheres was usually reflected by increases in AST, GGT, ALT and bilirubin levels [6,23,24]. The results of this study showed that AST, ALT and GGT levels did not change significantly after TACE compared with baseline, whereas ALK levels significantly increased versus baseline (though never exceeding normal values).…”
Section: Discussionsupporting
confidence: 90%
“…Treatment with LifePearl™ was well tolerated in the authors' study and agreed with the findings of several previous studies, which demonstrated good procedure safety and AEs of mild intensity (e.g., postembolic syndrome and fever) [ 6 , 17–25 ]. Liver toxicity with TACE with doxorubicin-loaded microspheres was usually reflected by increases in AST, GGT, ALT and bilirubin levels [ 6 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Polyethylene glycol offers a longer time in suspension than DC Bead and HepaSphere when loaded with doxorubicin and DC Bead and Tandem when loaded with irinotecan. Longer time in suspension enables a smoother embolization procedure without the need for any interruption to resuspend the microspheres [30] .…”
Section: Lifepearlmentioning
confidence: 99%